Higher spin generalisation of Fueter's theorem. (15th April 2018) - Eelbode, David; Janssens, Tim
Abstract : In this paper, we generalize Fueter's theorem to the higher spin setting. To do so, we consider an alternative proof for the celebrated theorem that uses the Fischer decomposition. This decomposition is then extended to spaces of polynomials that depend on wedge variables, after which we can finish the proof of our higher spin Fueter theorem.